2014
DOI: 10.1063/1.4899196
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulations of Taylor-Couette-Poiseuille flows in a narrow-gap system

Abstract: International audienceThe present paper concerns Large-Eddy Simulations (LES) of turbulent Taylor-Couette-Poiseuille flows in a narrow-gap cavity for six different combinations of rotational and axial Reynolds numbers. The in-house numerical code has been first validated in a middle-gap cavity. Two sets of refined LES results, using the Wall-Adapting Local EddyViscosity(WALE) and theDynamic Smagorinsky subgrid-scale models availablewithin an in-house code based on high-order compact schemes, have been then com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…In the bulk zone, the estimation by the numerical model is much better compared to the boundary layer, but still comparatively under-predicting. Chung & Sung [26], Poncet, Haddadi and Viazzo [27] and Poncet, Viazzo & Oguic [28] also observed similar results in the validation of their numerical models in both the boundary layer and bulk zone. For the VEDR of the mean flow kinetic energy (see Figure 4), it can be seen that the numerical model predicts the magnitude and the structure well in comparison with the experimental PIV estimations, especially in the boundary layer where the estimation is even comparatively higher.…”
Section: = + ( )supporting
confidence: 56%
See 1 more Smart Citation
“…In the bulk zone, the estimation by the numerical model is much better compared to the boundary layer, but still comparatively under-predicting. Chung & Sung [26], Poncet, Haddadi and Viazzo [27] and Poncet, Viazzo & Oguic [28] also observed similar results in the validation of their numerical models in both the boundary layer and bulk zone. For the VEDR of the mean flow kinetic energy (see Figure 4), it can be seen that the numerical model predicts the magnitude and the structure well in comparison with the experimental PIV estimations, especially in the boundary layer where the estimation is even comparatively higher.…”
Section: = + ( )supporting
confidence: 56%
“…Kobayashi et al [24] stated that this phenomenon is because of uniformity in the circumferential velocity, in which the velocity profiles apart from the ones in the outward and inward region are very similar to the one in the center of vortex region, which in turn is caused by convection of the secondary flow. In-fact, none of the numerical studies [18,20,[26][27][28] demonstrated the capability of the various numerical models to capture this phenomenon exhibited by experimental methods. In the case of the radial component (see Figure 2), though the magnitude is less than 3 % of the tangential component and the shape is well predicted by the numerical model, the maximum difference between the two axial heights is approximately 25 %.…”
Section: = + ( )mentioning
confidence: 99%
“…The numerical approach is based on the Reynolds Stress Modeling (RSM) where correlations for the averaged Nusselt numbers along both cylinders are finally provided according to the flow control parameters Reynolds number, friction coefficient and Prandtl number. In the work of Poncet et al [5] Large Eddy Simulations of Taylor-Couette-Poiseuille flows in a narrow gap system are presented together with a correlation for the Nusselt number along the rotor which shows a much larger dependence on the axial Reynolds number than expected from previous published works, while it depends classically on the Taylor number to the power 0.145 and on the Prandtl number to the power 0.3 i.e. Nu-Ta 0.145 Pr 0.3 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the superposition of an axial flow, known as Taylor-Couette-Poiseuille flow, has been used as an efficient mechanism to stabilize the basic flow (Snyder, (1962); Meseguer and Marques, (2002);Campero and Vigil, (1999); Poncet et al, (2014)). …”
Section: Introductionmentioning
confidence: 99%